Development of a Traditional Game Module to Improve Children's Self-Control Character Skills - Liswantiani, Ester; Wibowo, Setiawan Edi; Nugrahanta, Gregorius Ari (QALAMUNA: Jurnal Pendidikan, Sosial, dan Agama, 2024)
This research intends to guide teachers in developing self-control in children aged 9-12 through traditional games. The research method used was Research and Development (R&D) with the ADDIE framework (Analyze, Design, Develop, Implement, and Evaluate) involving six teachers, seven module validators, and six children. The research findings are as follows: The module received a "very good" rating with a score of 3.40 from one lecturer and five teachers. The surface and content validity tests received a "very good" rating of 3.50 and 3.55, respectively. 3) The application of the module has a positive effect on the self-control of children aged 9-12 years, with a high level of effectiveness of 88.70%. The research results showed that after using the module, the average posttest score (M = 0.9217) was higher than the pretest score (M = 0.6650). This difference is significant, with a value of tt(5) = 4.122, p = 0.009 (p <0.05). This module also has quite a big influence, with an effect size (r) of 0.88 or the equivalent of around 77.26%. In other words, the module has a fairly large role, contributing 77.26% to increasing self-control. The effectiveness of implementing the module is further proven by the N-gain score of 88.7073%, which shows a high level of effectiveness. Thus, this research provides a strong empirical basis for developing better educational programs, especially in improving self-control in children aged 9-12 through a traditional game approach.